Progressive damage and failure analysis of three-dimensional braided composites under multiaxial loadings. (1st November 2022) - Hu, Xinyu; He, Chunwang; Ge, Jingran; Zhang, Qi; Liang, Jun
Abstract: A meso-mechanical computational model based on the finite element method (FEM) is developed to predict the progressive elastic-plastic damage and failure behavior of three-dimensional four directional (3D4D) braided composites under multiaxial loadings. Firstly, the constitutive laws for mesoscale constituents (i.e. yarn, matrix and interface) of braided representative volume element (RVE) are established and implemented by the user defined material subroutine UMAT in ABAQUS. Then, how to build the braided RVE and conduct the simulation are introduced. After that, the uniaxial tensile data is used to verify the proposed model. Finally, the damage and failure behavior of the RVE under multiaxial loadings is investigated, considering the effects of loading paths and interface. The results show that loading path and interface have little effect on the strengths. The predicted failure envelopes in different stress spaces for RVE are compared with the Tsai-Wu and Hoffman theories, which are much closer to the Tsai-Wu theory.